THE EFFECT OF WORK-LIFE BALANCE AND COMPETENCE ON EMPLOYEE PERFORMANCE, MEDIATED BY INTRINSIC MOTIVATION, AMONG EMPLOYEES IN THE GENERAL AFFAIRS DIVISION OF THE MADIUN CITY REGIONAL SECRETARIAT - Dian Noervitasari; Rahayu Puji Suci; Choirum Rindah Istiqaroh; Muryati; Sodik (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the influence of work-life balance and competence on employee performance, with intrinsic motivation serving as a mediating variable, among employees of the General Affairs Division of the Regional Secretariat of Madiun City. The increasing complexity of administrative responsibilities, the growing implementation of technology in public services, and the need to maintain a balance between work and personal life require employees to possess adequate competencies and high intrinsic motivation to achieve optimal performance. However, several issues remain, including work-life imbalance, uneven employee competencies, and relatively low intrinsic motivation, all of which may affect employee performance.  This study employed a quantitative approach using an explanatory research design. The population consisted of all employees of the General Affairs Division of the Regional Secretariat of Madiun City. A census sampling technique was applied, in which all members of the population were included as research respondents. Data were collected through questionnaires using a Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both the direct and indirect relationships among the research variables. The results indicate that work-life balance has a positive and significant effect on both employee performance and intrinsic motivation. Competence has a positive and significant effect on intrinsic motivation but does not have a significant direct effect on employee performance. Intrinsic motivation has a positive and significant effect on employee performance. Furthermore, intrinsic motivation significantly mediates the relationship between work-life balance and employee performance through partial mediation, and fully mediates the relationship between competence and employee performance through full mediation. These findings suggest that improving employee performance depends not only on enhancing competence and maintaining work-life balance but also on strengthening employees' intrinsic motivation.